+0  
 
0
240
1
avatar

a - c/x - a = m

Guest Aug 20, 2017
 #1
avatar+178 
+1

Input : a - c/x - a = m

Intepretation: \(a-\frac{c}{x}-a=m\)

Cancel the \(a\) out on the left side:

\(-\frac{c}{x}=m\)

Multiply both sides by \(x\):

\(-c=mx\)

Divide both sides by \(m\):

\(x=-\frac{c}{m}\)

Done :)

Jeffes02  Aug 20, 2017

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.